Effects of fermented Yupingfeng on intramuscular fatty acids and ruminal microbiota in Qingyuan black goats. (2nd May 2021) - Yang, Hong; Tan, Shuwen; Chen, Siyu; Wu, Yongliang; Yang, Ying; Li, Hua; Yu, Hui
Abstract: Our previous work has demonstrated that Yupingfeng, a Chinese herb medicine, considered as prebiotic showed beneficial properties in poultry health and disease prevention and regulated intestinal microbiota. The effects of Yupingfeng on fatty acids related to meat flavor and ruminal microbiota are not yet known in Qingyuan black goat. In this study, we supplemented fermented (FYP) and unfermented (UYP) Yupingfeng in different combinations to 90 goats. Compared with the normal control group, FYP and UYP significantly increased the concentration of palmitic acid, octadecanoic acid, and arachidonate acid (related to meat flavor) in the longissimus dorsi muscle ( p  < .05). In addition, the significant upregulation of peroxisome proliferator‐activated receptor gamma ( PPARγ ) and fatty acid translocase ( CD36 ) was observed in the FYP and UYP groups ( p  < .05). In addition, Firmicutes and Bacteroidetes were the most abundance in goat rumen. At the genus level, FYP and UYP significantly increased Ruminococcus related to fiber degradation, and Alistipes related to short‐chain fatty acids production. In summary, Yupingfeng could improve fatty acids of goat meat, which is probably triggered by the increase of PPARγ and CD36, and microbial activity. Besides, FYP showed more beneficial effects than UYP, with increased flavor fatty acids and beneficial microbes.